Criticism of Fazlur Rahman's Al-Qur'an Hermeneutics - Femy, Femmy Putri Nursyifa; Naqiya, Hilya Nuri; Nur Azizah; Rofi Muttaqin, Muhammad; Purwati, Puji (Institut Agama Islam Persis Bandung, 2023)
Fazlur Rahman is a man who has various thoughts related to the issue of the Qur'an and Hadith, Rahman's presence in the list of names of Islamic thinkers brings something new to the renewal of Islam. Appear as a brilliant figure in formulating the method of interpretation of the Koran. Fazlur Rahman provides a more convincing method of interpretation, which lies in the use of philosophy, social sciences and humanities. The conceptual framework that Rahman built is often called the double movement hermeneutics. This is because in the process it involves a double movement, namely from the problem of the present situation to the time the Koran was revealed and from the time of the Koran back to the present problem. In this method the emphasis is on the basic ideas of the Koran or its moral ideals compared to the specific legal. Another term in the meaning that Fazlur Rahman puts forward the content of the universal meaning rather than the literal-particular meaning. The method formulated by Rahman finally not only contributed to the development of the Qur'anic interpretation method, but also influenced the ijtihad process in the context of answering the social-religious problems of the present era.